The Importance of C4d in Biopsies of Kidney Transplant Recipients - Rosana Rosa Miranda Corrêa; Juliana Reis Machado; Marcos Vinícius da Silva; Fernanda Rodrigues Helmo; Camila Souza Oliveira Guimarães; Laura Penna Rocha; Ana Carolina Guimarães Faleiros; Marlene Antônia dos Reis (Clinical and Developmental Immunology)
Antibody-mediated rejection (AMR) is highly detrimental to the prolonged survival of transplanted kidneys. C4d has been regarded as a footprint of AMR tissue damage, and the introduction of C4d staining in daily clinical practice aroused an ever-increasing interest in the role of antibody-mediated mechanisms in allograft rejection. Despite the general acceptance of the usefulness of C4d in the identification of acute AMR, the data for C4d staining in chronic AMR is variable. The presence of C4d in the majority of the biopsies with features of chronic antibody-mediated rejection is reported, but this rejection without C4d staining is observed as well, suggesting that C4d is specific but not sensitive. Further studies on AMR with positive C4d staining in biopsy specimens are really important, as well as the study of novel routine markers that may participate in the pathogenesis of this process.